PERAN SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG OPERASIONAL LAYANAN PELANGGAN PADA TIKTOK SHOP - Gilang Harshavardhana; Nur Alam Saputra; Rangga Al Fatah Said; Muhammad Syahrul Badawi; Akmal Fadilah Efendi (Media Riset Bisnis Manajemen Akuntansi, 2026)
The development of digital technology has transformed the way businesses operate, particularly on social media platforms such as TikTok, which now functions not only as an entertainment medium but also as a marketplace through the TikTok Shop feature. This study aims to analyze the role of Management Information Systems (MIS) in supporting customer service operations on TikTok Shop. The main focus of this research includes operational efficiency, customer data management, information quality, and user satisfaction. The analysis shows that MIS plays a significant role in enhancing the operational effectiveness of TikTok Shop through data integration, real-time transactions, and strong information security. In addition, ease of use, service quality, and perceived benefits contribute positively to customer satisfaction. TikTok Shop also utilizes cloud-based technology and data analysis algorithms to provide a more personalized and secure shopping experience. Overall, the effective implementation of MIS has been proven to improve business efficiency while strengthening customer loyalty toward the platform. Keywords : E-Commerce, Kepuasan pelanggan, Sistem informasi manajemen, Tiktok, Tiktokshop.